Cash Waqf through Islamic Banks: An Interpretive Structural Model (ISM) Framework - Aam Slamet Rusydiana; Ririn Riani; Denizar Mi'raj (International Journal of Waqf, 2022)
This research aims to identify the priority factors that are barriers to developing the practice of cash waqf through Islamic financial institutions in Indonesia using the Interpretive Structural Modeling (ISM) method. The development of cash waqf through Islamic banks in Indonesia with ISM framework is divided into three criteria: (1) Challenges (aspects) faced in developing cash waqf, (2) Strategy or foundation required within the framework of developing cash waqf, and (3) Stakeholders or actors involved in the development of cash waqf in Indonesia. The result show that the core problems and challenges faced in the development of cash waqf institutions are: System aspect, product, regulation, and information technology. The core strategies or foundations that are needed in the framework of cash waqf development are transparency and accountability of waqf institutions, Quality development of nadzir, and Innovative marketing strategy from waqf institutions. Government and Badan Wakaf Indonesia are stakeholders or actors involved and related to the development of cash waqf in Indonesia.